Talent Management Strategies in Responding to Industry 5.0 Disruption: A Competency- and Agility-Based Human Resource Development Model - Firdiansyah Lukman (PT. Anagata Sembagi Education, 2026)
The transition to Industry 5.0 requires organizations to adopt human-centered and sustainable strategies in managing their workforce. Talent management is no longer an administrative function but a strategic mechanism for developing competencies and agility to sustain competitive advantage. This study aims to analyze how competency-based talent management integrated with agility as a dynamic capability forms an effective human resource development model in responding to Industry 5.0 disruption. This research employs a quantitative explanatory design using a cross-sectional survey of managers and HR professionals in digitally transforming organizations. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling to test direct and mediating relationships among competency-based talent management, agility, and sustainable competitive advantage. The findings reveal that competency-based talent management significantly influences agility, and agility significantly enhances sustainable competitive advantage. Moreover, agility partially mediates the relationship between competency-based talent management and sustainable performance, indicating that competencies must be activated through adaptive capabilities to generate long-term value. The study concludes that integrating competency development with agility-building mechanisms is essential for achieving sustainable competitiveness in the Industry 5.0 era.